Gordon Research Conference on Radiation Chemistry, 1971 - Gordon Research Conferences (1971)
Group photograph of attendees at the Gordon Research Conference on Radiation Chemistry in New Hampton, New Hampshire in July 1971. Included with the photograph are a hand-drawn key and name list identifying the individuals depicted in the photo.
Keywords: Gordon Research Conferences; Portraits, Group; Congresses and conventions